Caring as Country: Towards an ontology of co‐becoming in natural resource management. (6th August 2013) - Suchet‐Pearson, Sandie; Wright, Sarah; Lloyd, Kate; Burarrwanga, Laklak
Abstract: This collaboratively written paper takes the reader on a journey to Bawaka, in North East Arnhem Land, northern Australia, to explore how a Yolŋu ontology of co‐becoming can inform natural resource management (NRM) theory and practice. By focusing on the process of gathering and sharing miyapunu mapu (turtle eggs) and the foundational Yolŋu concept of wetj, we challenge NRM to take seriously Indigenous ways of knowing and becoming, and to attend to the vibrant, more‐than‐human relationality of our world. We discuss this relational cosmology, highlighting the importance of being aware and attentive, as well as the underlying ethical imperative of responsibility and obligation. We argue that as important as the concept of Caring for Country has been for NRM in Australia, it is critical that the human imperative to care for Country is balanced with a multi‐directional and beyond‐human understanding of the human–Country relationship. This requires engagement with the ways Country also cares and acknowledgement that humans are part of Country and not separate from it. We therefore propose a reframing, that we not only Care for Country but Care as Country. This has implications for understanding the ways that humans can and should relate to the environment as they exist together through co‐becoming.